Volume 10: Micro and Nano Systems 2010
DOI: 10.1115/imece2010-38347
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Interstitial Velocity Field Inside Micro-Porous Media

Abstract: An investigation of interstitial velocity field within a micro porous media is studied using a three component three dimensional (3C3D) μ-PIV system. The porous media is formed by packing of micro glass beads of size 400 μm inside a flow cell. The two component two dimensional (2C2D) velocity fields in micro pore region are obtained near the wall. 3C3D velocity field is obtained by scanning through 100 μm inside the porous media using the scanning μ-PIV system. Cross flow pattern and flow recirculation is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, using the scanning stage one can extend this study to a three component threedimensional case. A preliminary result of such study was already reported by Sen et al (2010). Results of such studies can be useful in calculating the key transport properties like permeability in a microporous media.…”
Section: Image Processing and Vector Field Calculationmentioning
confidence: 82%
See 1 more Smart Citation
“…However, using the scanning stage one can extend this study to a three component threedimensional case. A preliminary result of such study was already reported by Sen et al (2010). Results of such studies can be useful in calculating the key transport properties like permeability in a microporous media.…”
Section: Image Processing and Vector Field Calculationmentioning
confidence: 82%
“…A flow cell is designed using commercial designing software (Dassault Systemes SolidWorks Corp, Solidworks 2009) and is manufactured using a rapid prototype (Objet, Eden 350) technique (Sen et al 2010). A sectional view of the flow cell is shown in Fig. 1b.…”
Section: Methodsmentioning
confidence: 99%